Depressive symptoms in late life: a 10-year follow-up - Heikkinen, Riitta-Liisa; Kauppinen, Markku (Archives of gerontology and geriatrics, 2004)
The objectives of this study were to describe the changes occurring in depressive symptomatology over a 10-year period among 75-year-old residents of Jyväskylä, Finland. It also addressed the question of whether the mood disturbances detected were a permanent phenomenon or whether they had a more episodic nature. In addition, various associations with and predictors of low mood were studied. Depressive symptoms were screened with the Center for Epidemiologic Studies Depression Scale (CES-D).The cut-off point of 16 was used to distinguish depressed individuals from those classified as non-depressed. A baseline study was carried out in 1989 ( n=337). A 5-year follow-up was carried out with the same cohort in 1994 ( n=222) and a 10-year follow-up in 1999 ( n=131). The permanent versus episodic nature of depressed mood was studied by comparing the three-wave longitudinal depression score findings of different individuals. In the follow-up settings, multivariate logistic regression models adjusted for sex were used to find predictors of depressiveness. Looking at the prevalence of depressiveness we found a statistically significant increase in the figures for women particularly from age 80 to 85 years. The much lower mean scores recorded for men in earlier measurements reached the same level as for women at age 85 years. Loneliness, a large number of chronic diseases, poor self-rated health, poor functional capacity, poor vision and perceived negative changes in life predicted depressive symptomatology. It seemed that minor depression among the elderly was most typically an episodic phenomenon.